Terminal illness... computer-related injuries. - Dooling S (Canadian Nurse, 1993)
Computers proliferate in almost every workplace of today. Unfortunately, society seems to have been more interested in mass-producing computer systems than in the health and comfort of the humans who interact with them. The unhappy consequence has been a growing rate of computer-related injuries. Nursing worksites are far from immune to this 'terminal' illness; the health hazards associated with radiation, stress and workplace design have brought ill health to nurses and to other workers. But like other health problems, computer-related illness can be avoided through preventive care.